Regeneration Potential Of Bentonite Based Thin Coated Adsorbent - Momina, Momina (2019)
Adsorption is one of the widely used method for wastewater treatment since it is cost-effective, eco-friendly and highly efficient in nature. Bentonite based adsorbent coating was introduced to overcome the problem associated with the use of adsorbents in pellet, beads, powder, or other particle forms. Its adsorption capacity increases due to increase in surface area/weight ratio. It is important to regenerate adsorbent before it is disposed into environment. Therefore, this study is focused on regeneration of bentonite-based coating using three different methods; chemical regeneration, thermal regeneration and combination of thermal and chemical (thermo-chem) regeneration. Chemical regeneration was not found to be suitable for the regeneration of bentonite adsorbent coating with 22% desorption efficiency of MB using ethanol. Rather, thermal effect can loosen the bonds between adsorbate and adsorbent, but unable to completely break the bond between MB and adsorbent coating at 160oC. The thermo-chem method effectively desorbed MB with desorption efficiency of 74 % using HCl after heating adsorbent coating at 160 oC for initial dye concentration of 50 ppm. Also, regeneration study results confirm successive adsorption/desorption of MB on adsorbent coating even after 7th cycle. The characterization of PaintosorpTM before and after desorption of dye has been performed using TGA/DTA, SEM, EDX, BET, PSD and FTIR analysis. Batch desorption study of MB results Sips and Freundlich isotherm model are best fitting which shows that desorption of MB occurs from multilayer adsorbed MB on adsorbent coating. However, kinetic model best fitting with pseudo second order model and confirms that desorption mechanism is due to concentration gradient, solubility and diffusivity of MB.